2017
DOI: 10.1021/acs.nanolett.7b02461
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Silica Nanoparticles Penetrate the Peripheral Nerve and Enhance the Nerve Blockade from Tetrodotoxin

Abstract: The efficacy of tetrodotoxin (TTX), a very potent local anesthetic, is limited by its poor penetration through barriers to axonal surfaces. To address this issue, we encapsulated TTX in hollow silica nanoparticles (TTX-HSN) and injected them at the sciatic nerve in rats. TTX-HSN achieved an increased frequency of successful blocks, prolonged the duration of the block, and decreased the toxicity compared to free TTX. In animals injected with fluorescently labeled HSN, the imaging of frozen sections of nerve dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…[ 31 ] Finally, frozen sections were carried out to determine the delivery efficiency of NPs loading agents into intratumor and cellular permeation. [ 32 ] We found that N‐NP‐Cy2 and P‐NP‐Cy2 showed little intratumor cell penetration. In consistent with imaging in vivo, O‐NP‐Cy2 exhibited high accumulation in the LS180 tumor and notably cellular penetration (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] Finally, frozen sections were carried out to determine the delivery efficiency of NPs loading agents into intratumor and cellular permeation. [ 32 ] We found that N‐NP‐Cy2 and P‐NP‐Cy2 showed little intratumor cell penetration. In consistent with imaging in vivo, O‐NP‐Cy2 exhibited high accumulation in the LS180 tumor and notably cellular penetration (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…MSN drug carriers have been developed for a wide variety of therapeutic applications, such as anesthesia [ 48 ], infection [ 49 , 50 ], osteoporosis [ 51 ] and allergy [ 52 ], among others. However, the most studied application by far is cancer therapy [ 53 ], developing MSNs to deliver anticancer drugs such as doxorubicin [ 37 , 54 , 55 , 56 , 57 , 58 ], camptothecin [ 59 ], topotecan [ 60 ], paclitaxel [ 61 ], gemcitabine [ 62 ], and 5-fluorouracil [ 63 ].…”
Section: Mesoporous Silica Nanoparticles For Drug Deliverymentioning
confidence: 99%
“…The efficacy of NaV channels in blocking toxins, including TTX, is limited due to their relatively weak penetration to the site of action through different tissue barriers [ 70 ]. High concentrations of the toxin are required to overcome these barriers and to achieve sufficient levels and duration of the nerve fibers to induce a blocking effect, which can lead to significant systemic toxicity [ 71 ].…”
Section: Ttx Co-application and Address Deliverymentioning
confidence: 99%
“…Adams et al showed that the simultaneous administration of TTX with various local anesthetics (procaine, lidocaine, tetracaine, cinchocaine, cocaine, and bupivacaine) increased the sciatic nerve block rate to 100% and prolonged its average duration by 2.5–5 times in comparison with the test anesthetics alone [ 75 ]. Several studies have also shown the beneficial effect of bupivacaine on the nerve block caused by the administration of TTX, depending on the toxin concentration [ 70 , 71 , 76 ]. Such a synergistic effect on cornea anesthesia in rats, caused by TTX together with proparacaine, was also observed in other studies [ 74 ].…”
Section: Ttx Co-application and Address Deliverymentioning
confidence: 99%
See 1 more Smart Citation